Early development and osteoporosis and bone health. - Dennison, E; Cooper, C; Cole, Z (2010)
Osteoporosis is a skeletal disorder characterized by low bone mass and micro-architectural deterioration of bone tissue with a consequent increase in bone fragility and susceptibility to fracture. Evidence is now accumulating from human studies that programming of bone growth might be an important contributor to the later risk of osteoporotic fracture. Body weight in infancy is a determinant of adult bone mineral content, as well as of the basal levels of activity of the growth hormone/insulin-like growth factor-1 (GH/IGF-1) and hypothalamo-pituitary-adrenal (HPA) axes, and recent work has suggested a central role for vitamin D. Epidemiological studies have shown that maternal smoking and nutrition during pregnancy influence intrauterine skeletal mineralization. Childhood growth rates have been directly linked to the risk of hip fracture many decades later, and now evidence is emerging from experimental animal studies that support these observational data. Recent studies have also highlighted epigenetic phenomena as potential mechanisms underlying the findings from epidemiological studies.